Research on consistency protection mechanism for secure states of virtual domain in cloud environment - Wei-qi DAI; De-qing ZOU; Hai JIN; Yan XIA (网络与信息安全学报)
The traditional trusted computing architecture was suffering from the cloud uncertainty and dynamics caused by VM rollback or migration,which was a fatal threat to the cloud security.following investigations were conducted.Secure cloud virtual domain basic architecture; Time state consistence and collection mechanism.Cyber state consistence and collection mechanism.This study guaranteed security state consistence of virtual domain and improved the security and efficiency of the online service platform for both government institutions and companies.